Different modelling and simulation approaches for food processing operations - Rauh, Cornelia; Delgado, Antonio (Modeling Food Processing Operations, 2015)
This chapter discusses modelling and simulation strategies in food science and technology. To this end, it focuses on the selection of models based on available system knowledge and complexity. First, the chapter presents some basic aspects of food processing with particular relevance for modelling and simulation. Then it introduces various balancing, knowledge-oriented and hybrid approaches to modelling and simulating food processing. In order to illustrate these approaches, the authors provide examples of state-of-the-art and emerging technologies, such as ultra-high-pressure processing and pulsed electric fields processing. The chapter's final section summarises up-to-date methods and discusses the most promising future modelling and simulation approache
UnivIS-Import:2016-06-01:Pub.2015.tech.ITC.stmmec.differ
Keywords: Modelling and simulation strategies for food processing; Limitations of modelling and simulation; Computational fluid mechanics; Cognitive algorithms; Hybrid methods